2018
DOI: 10.1039/c7ob02558k
|View full text |Cite
|
Sign up to set email alerts
|

The role of catalytic residue pKa on the hydrolysis/transglycosylation partition in family 3 β-glucosidases

Abstract: β-Glucosidases (βgls) primarily catalyze the hydrolysis of the terminal glycosidic bond at the non-reducing end of β-glucosides, although glycosidic bond synthesis (called transglycosylation) can also occur in the presence of another acceptor. In the final reaction step, the glucose product or another substrate competes with water for transfer to the glycosyl-enzyme intermediate. The factors governing the balance between the two pathways are not fully known; however, the involvement of ionizable residues in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…This modification almost certainly affects the protonation capability of E176 and thus impairs the ability of the enzyme to activate incoming acceptors (irrespective of whether it is a water molecule or a glycoside acceptor). In turn, it can be postulated that this partially diminishes the thermodynamic advantage of water (although water concentration remains a determining factor), and concomitantly increases the likelihood of deglycosylation by glycoside acceptors (pKa of xylose = 12.15) [69], which display lower deprotonation enthalpy than water [70]. Finally, it is also relevant to note that N175 is thought to be involved in TS stabilization [39].…”
Section: The Conserved Residue R69 Plays a Key Role In T/h Modulationmentioning
confidence: 99%
“…This modification almost certainly affects the protonation capability of E176 and thus impairs the ability of the enzyme to activate incoming acceptors (irrespective of whether it is a water molecule or a glycoside acceptor). In turn, it can be postulated that this partially diminishes the thermodynamic advantage of water (although water concentration remains a determining factor), and concomitantly increases the likelihood of deglycosylation by glycoside acceptors (pKa of xylose = 12.15) [69], which display lower deprotonation enthalpy than water [70]. Finally, it is also relevant to note that N175 is thought to be involved in TS stabilization [39].…”
Section: The Conserved Residue R69 Plays a Key Role In T/h Modulationmentioning
confidence: 99%
“…Transglycosylation is a major limiting factor for HjCel3A, but this can be mitigated by point mutations of residues responsible for cellobiose and glucose affinity at the product site, specifically Trp-37, Phe-260, and Tyr-443. This is another approach in addition to elevating the pK a of Glu-441 as we proposed in the recent constant-pH MD study (30). Finally, HjCel3A's sequence similarity with xylosidic GH3s suggests that xylosidase activity can be conferred with relatively small modifications to the active site; this is advantageous in potentially reducing the number of enzyme components required in cellulase mixtures.…”
Section: Inhibition and Transglycosylation In H Jecorina Cel3a/bmentioning
confidence: 93%
“…A constant-pH MD study of HjCel3A-GEI (with or without glucose in the ϩ1 site) indicated that Glu-441 has a very low pK a (ϳ2) due to hydrogen bond networks with Arg-125 and Arg-169. The low basicity of Glu-441 would reduce its ability to deprotonate water, which has a higher deprotonation enthalpy than sugars (30). In contrast, HjCel3B homology modeling showed negatively charged residues (Glu-211, Glu-454, and Glu-525) situated within 10 Å of Glu-516 ( Fig.…”
Section: Inhibition and Transglycosylation In H Jecorina Cel3a/bmentioning
confidence: 98%
“…The criterion for selecting residues for mutagenesis was if the original residue in TmAmyA had an enrichment value (∆ f ij aa ) below −0.2 (residues enriched in hydrolases) or if the ∆ f ij aa for potential candidate residues was above 0.2 (enriched in transferases), while the TmAmyA residue had a ∆ f ij aa ≤ 0. A valuable result from this approach was the identification of targets for mutagenesis beyond the catalytic site, whose relevance in terms of their specificity and activity has been shown by directed evolution [41]. The exploration of such sites is limited by the availability of selection or high-throughput screening methods; thus, restricting the sequence space that is to be evaluated becomes paramount.…”
Section: Modification Of Reaction Specificity In the α-Amylase A From Termotoga Maritmamentioning
confidence: 99%
“…However, the pKa increase of the acid-baseresidue may be more relevant for the hydrolysis than for the transglycosylation reaction, since proton removal from a water molecule is energetically more demanding. Recently, Geronimo et al [41] reported a molecular dynamic simulation at a constant pH for beta-glycosidase (bglc) from Hypocrea jecorina. Using this approach, the authors observed that the usual rearrangement of the active center (residues R169, Y204, and W237) is different if acceptor nucleophiles like cellobiose or glucose are present.…”
Section: Introductionmentioning
confidence: 99%